2006
DOI: 10.1016/j.visres.2005.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Progressive N170 habituation to unattended repeated faces

Abstract: This study utilized a location-matching task to investigate whether the face-sensitive N170 event-related potential component would habituate in its response to the repeated presentation of same face stimuli when face identity was irrelevant to the experimental task. N170 amplitude decreased progressively with repeated presentation of the same face vs. sequential presentation of novel faces. This N170 habituation to face identity repetition occurred only for faces at unattended spatial locations, likely repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
32
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 32 publications
16
32
2
Order By: Relevance
“…Previous studies using famous faces reported comparable lack of the N170 repetition effect (Henson et al, 2003;Caharel et al, 2002;Schweinberger, Pickering, Jentzsch, et al, 2002) and when unfamiliar faces were used in similar paradigms the N170 repetition effect was observed (Heisz et al, 2006a(Heisz et al, , 2006bItier & Taylor, 2002, 2004Guillaume & Tiberghien, 2001;Campanella et al, 2000;George, Jemel, et al, 1997). In the present study, prior to face learning, all faces were unfamiliar and elicited the N170 repetition effect.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous studies using famous faces reported comparable lack of the N170 repetition effect (Henson et al, 2003;Caharel et al, 2002;Schweinberger, Pickering, Jentzsch, et al, 2002) and when unfamiliar faces were used in similar paradigms the N170 repetition effect was observed (Heisz et al, 2006a(Heisz et al, , 2006bItier & Taylor, 2002, 2004Guillaume & Tiberghien, 2001;Campanella et al, 2000;George, Jemel, et al, 1997). In the present study, prior to face learning, all faces were unfamiliar and elicited the N170 repetition effect.…”
Section: Discussionsupporting
confidence: 73%
“…ERPs were recorded before and after learning, and we were interested in learning-induced changes in the N170, an ERP component primarily implicated in perceptual face processing (Carmel & Bentin, 2002;Sagiv & Bentin, 2001;Eimer, 2000b;Bentin et al, 1996). We expected a change in the N170 repetition effect, which is characterized by a reduction in the N170 amplitude following immediate presentations of the same face (Heisz et al, 2006a(Heisz et al, , 2006bItier & Taylor, 2002, 2004Guillaume & Tiberghien, 2001;Campanella et al, 2000;George, Evans, et al, 1997;George, Jemel, et al, 1997). The N170 repetition effect is observed for unfamiliar faces but not familiar faces (Henson et al, 2003;Caharel et al, 2002;Schweinberger, Pickering, Jentzsch, et al, 2002), therefore we expected the repetition effect to be reduced or eliminated following face learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to face processing, the right hemisphere dominance has been suggested in healthy subjects. For example, previous ERP studies have reported that the N170 face repetition effect was lateralized to the right hemisphere (Campanella et al 2000;Heisz et al 2006a). The N170 face repetition effect refers to N170 amplitude reduction when that face is repeated, compared to the presentation of unrepeated faces (Campanella et al 2000;Heisz et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous ERP studies have reported that the N170 face repetition effect was lateralized to the right hemisphere (Campanella et al 2000;Heisz et al 2006a). The N170 face repetition effect refers to N170 amplitude reduction when that face is repeated, compared to the presentation of unrepeated faces (Campanella et al 2000;Heisz et al 2006a). This repetition effect on the N170 has been proposed to reflect early identity processing that underlies the acquisition of familiarity for novel faces (Heisz et al 2006b).…”
Section: Introductionmentioning
confidence: 99%